Toefl iBT : (Learning express, 2006)
The TOEFL test is required for admission to English instruction-based universities. This book helps students thoroughly prepare for all components: reading comprehension skills, speaking, listening comprehension, and writing. Bundled with a CDROM and including a free online practice exam, TOEFL is based on the new Internet version of the test.